Karakteristik fisikokimia tepung jewawut (Setaria italica) varietas Polewali Mandar sebagai pengaruh frekuensi proses penyosohan - Handoko, Ari; Kusnandar, Feri; Budijanto, Slamet; Herawati, Heny (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Foxtail millet (Setaria italica var Polewali Mandar) is a common cereal crop in Polewali Mandar, with the potential for development as a food ingredient. This study characterizes millet from three varieties (Minna, Lasse, and Bulawang) polished 2, 3, and 4 times. Analysis of millet flour (80 mesh) includes chemical (proximate, dietary fiber, tannin), physical (color, pasting profile, granule shape using SEM), and starch digestibility. The data were evaluated using statistical analysis of variance (ANOVA), and the Tukey Honestly Significant Difference (HSD) Test was used if there was a significant result (p0.05) for each treatment. The results showed that polishing affected proximate, tannin, dietary fiber, and color but not digestibility and starch profile. Additionally, tannin content from Polewali Millet (0,016-0,026%) aligns with WHO and FAO standards. Foxtail millet has high dietary fiber (16-22%) compared to rice (0,1%). Millet flour colors vary, and starch digestibility is moderate (40-50%). Total starch is 50-60%, with amylose content of 4-5,9%. Pasting profile increases after polishing. Starch granules are round, oval, and polygonal with different sizes.